Hubungan Lama Kerja dan Penggunaan APD terhadap Kejadian ISPA pada Pekerja PT. Cakra Indo Pratama (CIP) Site Bukit Asam Tanjung Enim - Zairinayati; Muhammad Hafizd Al Razi (IKesT Muhammadiyah Palembang, 2024)
Background: Work duration of more than 5 years has a risk of experiencing symptoms of acute respiratory infections, acute respiratory infections are upper or lower tract diseases, usually infectious and cause various diseases that range from asymptomatic diseases or mild infections to severe and deadly diseases, the need for efforts for occupational safety in PT. CIP workers, Personal Protective Equipment is one of the last efforts for the company to protect its workforce from factors and potential hazards. The purpose of the study: To determine the relationship between length of work and the use of personal protective equipment to acute respiratory infections in PT. CIP field workers. Research Methods: Quantitative type research using analytical observations with a cross-sectional study approach. Results: research using Chi-Square found that the relationship between length of work with the incidence of acute respiratory infections obtained a p value = 0.391, between the use of personal protective equipment with the incidence of , acute respiratory infections obtained a p value = 0.001. Conclusion: There is no significant relationship between length of work and the incidence of acute respiratory infections, while there is a significant relationship between the use of personal protective equipment and the incidence of acute respiratory infections.